In Situ Structural Determination of a Homogeneous Ruthenium Racemization Catalyst and Its Activated Intermediates Using X‐Ray Absorption Spectroscopy. Issue 15 (25th February 2020) - Gustafson, Karl P. J.; Guðmundsson, Arnar; Bajnóczi, Éva G.; Yuan, Ning; Zou, Xiaodong; Persson, Ingmar; Bäckvall, Jan‐E.
Abstract: The activation process of a known Ru‐catalyst, dicarbonyl(pentaphenylcyclopentadienyl)ruthenium chloride, has been studied in detail using time resolved in situ X‐ray absorption spectroscopy. The data provide bond lengths of the species involved in the process as well as information about bond formation and bond breaking. On addition of potassium tert ‐butoxide, the catalyst is activated and an alkoxide complex is formed. The catalyst activation proceeds via a key acyl intermediate, which gives rise to a complete structural change in the coordination environment around the Ru atom. The rate of activation for the different catalysts was found to be highly dependent on the electronic properties of the cyclopentadienyl ligand. During catalytic racemization of 1‐phenylethanol a fast‐dynamic equilibrium was observed. Abstract : Resolved in situ ! The activation process of a known Ru‐catalyst, dicarbonyl(pentaphenylcyclopentadienyl)ruthenium chloride, is studied in detail using time resolved in situ X‐ray absorption spectroscopy. The data provide bond lengths of the species involved in the process such as the acyl type key intermediate as well as information about bond formation and bond breaking during the activation process.